ANALISIS PENGARUH DANA PIHAK KETIGA, BOPO, CAR, LDR DAN NPL TERHADAP KINERJA KEUANGAN PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yunia Putri Lukitasari; Andi Kartika (Jurnal Ilmiah Infokam, 2015)
The purpose of this research  is  to  examine  influence  of  Third  Party  Funds,  Operating Expanse  to Operating Income, Capital Adequacy Ratio, Loan  to Deposit Ratio, Non Performing Loan throught financial performance of public banking listed at Indonesian Stock Exchange during 2010-2012. Population of this research are Commercial  Bank  that  registered  in  Indonesian  Stock Exchange from 2010 till 2012. Data on this research are coming from Indonesian Stock Exchange (ISX). Sample are choosen by purposive sampling method at least 27 company. Data’s test technique by using multiple linear regression analyze. The result showed that the Thirt Party Funds, Capital Adequacy Ratio and Non Performing Loan has no effect on Return On Asset,Operating Expenses to Operating Income negatively effect the Return On Asset and Loan to Deposit Ratio has a positive effect on Return On Asset.Keyword:  Thirt  Party  Funds, Operating  Expense  to Operating  Income, Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loan And Return On Asset.